Going the distance: secrets to lifelong love - Barbach, Lonnie (Doubleday, 1991)
Presents the PBS Adult Learning Service's PBS Going the Distance Project. Provides information, references, and tools for educators to develop, enhance, and promote institution's distance degree program.